2022
DOI: 10.1155/2022/3705943
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Bitter Melon Extract on Growth Performance, Antioxidant Capacity, Inflammatory Cytokines Expression, and Intestinal Microbiota in Common Carp (Cyprinus carpio L.)

Abstract: Bitter melon extract (BME), which contains a variety of natural bioactive substances, has diversified biological functions. The present study is aimed at evaluating the effects of dietary supplementation of BME on growth performance, antioxidant capacity, inflammatory cytokine expression, and intestinal microbiota in common carp (Cyprinus carpio L.). An 8-week feeding trial was conducted using four isonitrogenous and isoenergetic diets containing different levels of BME (0%, 0.25%, 0.5%, and 1% for control, LB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The antioxidant defense system protects cells from oxidative damage and is closely related to the immune system and health status of fish [50,51]. In this study, fish fed a diet based on PHB showed a higher induction of SOD and CAT enzymes, especially in PHB-0.5 and PHB-1.0, compared to the control, and this indicates that PHB has the ability to enhance the antioxidant defense system in African catfish.…”
Section: Aquaculture Nutritionmentioning
confidence: 52%
See 1 more Smart Citation
“…The antioxidant defense system protects cells from oxidative damage and is closely related to the immune system and health status of fish [50,51]. In this study, fish fed a diet based on PHB showed a higher induction of SOD and CAT enzymes, especially in PHB-0.5 and PHB-1.0, compared to the control, and this indicates that PHB has the ability to enhance the antioxidant defense system in African catfish.…”
Section: Aquaculture Nutritionmentioning
confidence: 52%
“…Similarly, supplementation with the Chinese herbal medicine mixture significantly improved the activities of SOD and CAT in European eel [11] and Japanese seabass [17]. Other studies have also reported the enhancing effects of different herbs, singly or in combination, on the fish antioxidant enzyme system [4,12,44,51]. Therefore, the higher activities of SOD and CAT correspond to the higher heterophil counts recorded in PHB-0.5 and PHB-1.0, which means that PHB has the potential to modulate nonspecific immunity and antioxidant enzyme responses in African catfish, and this could be related to the biological active compounds present in the mixed herb.…”
Section: Aquaculture Nutritionmentioning
confidence: 84%
“…Meanwhile, after the stress, MDA decreased and CAT and SOD increased in the treated rainbow trout [ 25 ]. The enhancing effects of the plant's extracts on the fish antioxidant system have been reported in many spices like common carp treated with common mallow ( Malvae sylvestris ), oregano ( Origanum vulgare ), and Persian shallot ( Allium hirtifolium boiss) [ 49 ], coriander ( Coriandrum sativum ), common mallow ( M. sylvestris ) fed oak acorn ( Quercus brantii ) [ 50 ], bitter melon extract ( Momordica charantia ) [ 51 ], Nile tilapia fed thyme powder ( Thymus vulgaris ) [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that glucan endo-1,3-beta-glucosidase (BG-4), a 4 kilodaltons (kDa) peptide extracted from bitter gourd seeds using 70% ethanol, has exceedingly strong trypsin-inhibiting activity [86]. The findings of a murine study (RAW2642) investigating the impact of M. charantia on impaired glucose metabolism induced by lipopolysaccharide (LPS) revealed that M. charantia reduced the expression of inflammatory genes including Interleukin 6 (IL6), TNF-α, Interleukin 1 (IL1), cyclooxygenase-2(COX2), Inducible nitric oxide synthase (iNOS), and Interleukin 10 (IL10) [87]. Bitter melon extract (BME) inhibited IL-1 mRNA expression in the head kidney, spleen, and intestine of common carps, indicating that BME is a positive expression in inflammatory cytokines [88].…”
Section: Anti-inflammatory and Antioxidant Activitymentioning
confidence: 99%